Analysis Of Antibiotic Residue On Vaname Shrimp (Litopenaeus Vannamei) In Kalipuro Intensive Pond, Banyuwangi - Sapto Andriyono; Faridha Kusumaningrum; Suciyono Suciyono (Barakuda'45, 2022)
Antibiotics are compounds that are used to inhibit the growth of disease or are commonly referred to as drugs. Some examples of antibiotics most commonly used in shrimp culture are tetracycline, oxytetracycline, and chloramphenicol. In shrimp farming, antibiotics function as disease prevention or as a cure for the disease. But if the application is not under the dose, it will cause residues on the shrimp and harm human health if consumed. The purpose of this study was to determine the antibiotic content of tetracycline, oxytetracycline, and chloramphenicol in vannamei shrimp in intensive ponds in Kalipuro, Banyuwangi, East Java, and to determine the safety and feasibility of vannamei shrimp products consumed by the public based on the EDI (Estimated Daily Intake) and HQ (Hazzard) indexes. Quotients). The research was conducted using HPLC (High-Performance Liquid Chromatography) and ELISA (Enzyme-Linked Immunosorbent) methods to analyse the antibiotic content of vannamei shrimp then, the data obtained were processed using the EDI (Estimate Daily Intake) method to obtain daily estimates and HQ (Hazzard Quotient). to carry out an antibiotic risk assessment in the human body. The results obtained from this study were that vannamei shrimp in intensive ponds in Kalipuro, Banyuwangi, and East Java were negative for tetracycline, oxytetracycline, and chloramphenicol antibiotics. So the conclusion obtained from this study is that vannamei shrimp from intensive ponds in Kalipuro, Banyuwangi, and East Java is safe for consumption because it is negative for antibiotic residues.